Periodic Examination of Pregant Women at Tanjung Lalak Kotabaru Health Center Based on Information System - Salim, Yeffriansjah; Herliani, Ema; Hasan, Ryan Imelda (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Tanjung Lalak Health Center is located at Education street RT 1. TanjungLalak Selatan Village, Pulau Laut Kepulauan District, Kotabaru Regency. South Kalimantan. Tanjung Lalak Health Center has several poly services including: Pregnant/Obsig poly. Some of the services provided by the puskesmas for pregnant women who check themselves include obtaining the MCH book (Maternal and Child Health), a pink book that mothers must have. Usually the examination is only carried out by a midwife. By asking when the last menstruation started and finished before pregnancy to determine the estimated gestational age. The midwife will check blood pressure, measure arm circumference, and examine the condition of the pregnant woman's stomach. At the Tanjung Lalak Health Center there are no ultrasound facilities, so if you want to confirm the condition of the fetus, you have to visit an obstetrician or regional hospital. Of course this costs money because BPJS is not covered for USG except for emergency situations. The puskesmas midwife will provide free vitamins or supplements such as folic acid, calcium, and iron supplement tablets to support the growth of the fetus in the womb. In addition to vitamins, pregnant women get additional food in the form of biscuits with strawberry-flavored cream. The puskesmas will provide several cartons of biscuits for a few weeks' supply. These biscuits are consumed 2 to 3 pieces per day. The Tanjung Lalak Health Center requires blood tests for pregnant women. These tests include a blood test and checking sugar levels at least twice during pregnancy and are free of charge. The problem that will be discussed in this study is to record the history of examination of pregnant women and record supplies of vitamins/supplements, biscuits for pregnant women and medicines that are available for the Pregnant/Obsigin Polyclinic. The application will be made using database access with Visual Basic .net, the final conclusion of the application is that it can store data from midwives' examinations on pregnant women and print Maternal and Child Health Books, the application can print reports on the activities of the Pregnant Poly / Obstetrician Polyclinic every month as a general report every month to the Head of the Tanjung Lalak Health Center, as well as the application to automatically record the remaining supplies of vitamins, biscuits and medicines, and make it easier for the Tanjung Lalak Health Center Midwives to see the history of examinations of pregnant women and the administration of medicines, vitamins and biscuits.